Distribution and morphobiological characteristics of the chinese false gudgeon Abbottina rivularis (Basilewsky, 1855) in the Ile river basin (Balkhash basin, Republic оf Kazakhstan (Eurasian Journal of Ecology, 2022)
As a result of intentional and accidental introduction of alien fish species in most reservoirs of Southern and South–Eastern Kazakhstan, there was a significant change in the composition of the ichthyofauna. Alien low-value fish species have become numerous in many small reservoirs of the basin. In 2019-2021, the distribution of the river abbottina Abbottina rivularis (Basilewsky, 1855) was studied in several small reservoirs of the Ile River basin. The purpose of the research: to study the morphobiological characteristics of two populations of river abbotina in the basin of the Ile and give an assessment of their condition. Biological and morphological analyses of samples were carried out according to the most common scheme. The variability of 33 plastic and 7 counting features of two samples was studied. An indicator of fluctuating asymmetry was used to assess the conditions of existence. As a result of morphometric measurements of fish, out of 20 indicators of plastic measurements, significant changes were found in 9 (45%) plastic signs compared to the mother reservoir. In fish, the antedorsal distance (aD) increased by 6%, the length of the dorsal fin base (lD) by 25%, the height of the dorsal fin (hD) by 6.3%, the length of the anal fin (lA) by 51.4%, the length of the pectoral fins (lP) by 10.8%, the length of the ventral fin (lV) increased by 18%. The length of the head (c) increased by 11.2%, the highest body height (H) decreased by 5.3%, the lowest body height (h) increased by 26.4%. Despite significant violations of homeostasis in development, fish in ponds reach large sizes.Тhe Bakanas irrigation irrigation system can be a supplier of juvenile river abbotina for the Ile River. The size and weight indicators of the studied populations of the river abbotina from two samples showed lower values when compared with similar data from the Issyk River (1975) and the mother reservoir of the Amur River (1956).Key words: acclimatization, alien species, river abbotina, Balkhash – Ili basin, small reservoirs, morphometric characteristics, fluctuating asymmetry.